2017 Ieee Sensors 2017
DOI: 10.1109/icsens.2017.8234419
|View full text |Cite
|
Sign up to set email alerts
|

Pt-AlGaN/GaN HEMT-sensor layout optimization for enhancement of hydrogen detection

Abstract: This paper reports on the layout optimization of Pt-AlGaN/GaN HEMT-sensors for enhancing hydrogen sensor performance. Sensors with gate width and length ratios Wg/Lg from 0.25 to 10 were designed, fabricated and tested for the detection of hydrogen gas at 200 °C. Sensitivity, sensing current variation and transient response are directly related to the sensor gate electrode Wg/Lg ratio. The obtained results demonstrated a 217 % increase in sensitivity and 4630 % increase in sensing current variation at 500 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A Silicon carbide FET with Pt and Ir gates was also shown to sense H2S, however signal saturation was observed at low concentration of 6~8 ppm under 5% oxygen atmosphere [32]. Recently we presented successful sensing of H2S with Pt-AlGaN/GaN HEMT based sensor [33]. In this work, we further expand on our preliminary results by comprehensively studying DC and transient characteristics at different temperatures and H2S concentrations in dry air atmosphere.…”
Section: A C C E P T E D Mmentioning
confidence: 73%
See 1 more Smart Citation
“…A Silicon carbide FET with Pt and Ir gates was also shown to sense H2S, however signal saturation was observed at low concentration of 6~8 ppm under 5% oxygen atmosphere [32]. Recently we presented successful sensing of H2S with Pt-AlGaN/GaN HEMT based sensor [33]. In this work, we further expand on our preliminary results by comprehensively studying DC and transient characteristics at different temperatures and H2S concentrations in dry air atmosphere.…”
Section: A C C E P T E D Mmentioning
confidence: 73%
“…1. The gate dimensions exposed to gas were 40 μm × 400 µm and the gate-source and gate-drain spacing was 6 µm, based on our earlier report [36]. After fabrication, the wafers were diced and individual devices were wire bonded to ceramic substrates for high temperature measurements.…”
Section: Fabrication Of Sensorsmentioning
confidence: 99%
“…AlGaN/GaN-based sensors with gate electrodes of different W g /L g ratios (e.g., 1, 5, 7, 10, and 100) have been demonstrateded. 84,95,96,108 Sokolovskij et al 28,84 revealed that the dimensions of the gate electrode directly influence the sensitivity, current variations, and transient response of the sensor. As W g /L g was increased from 0.25 to 10, a 217% increase in the sensitivity and a 4630% increase in variations in the sensing current of the sensor were recorded under 500 ppm H 2 .…”
Section: Impact Of the Structure And Fabrication On Dynamic Responsesmentioning
confidence: 99%
“…Therefore, it is important to build a sensing device with high sensitivity. Since semiconductor-based HEMTs can easily achieve high sensitivity with small sizes, they are widely used in sensor systems [ 6 , 7 , 8 ]. HEMTs comprise a heterojunction structure, with wide and narrow bandgap layers.…”
Section: Proposed System Architecturementioning
confidence: 99%